The impact of tamsulosin on cognition in Alzheimer disease with benign prostate hyperplasia: A study using the Hallym Smart Clinical Data Warehouse. Issue 22 (29th May 2020) - Sohn, Jong-Hee; Lee, Sang-Hwa; Kwon, Young-Suk; Kim, Jong-Ho; Kim, Youngmi; Lee, Jae Jun
Abstract : Abstract: Studies suggest that the use of alpha-blockers increases the risk of dementia in patients with benign prostate hyperplasia (BPH). Due to study limitations, the relationship between the use of alpha-blockers, such as tamsulosin, and the risk of dementia is still unclear. However, alpha1-adrenoreceptors are also present in the brain, so there is potential for adverse effects on cognitive function. Therefore, we investigated possible associations between the use of alpha-blockers and aggravation of cognitive decline in dementia patients using a clinical data analytic solution called the Smart Clinical Data Warehouse (CDW). We retrospectively investigated clinical data using the Smart CDW of Hallym University Medical Center from 2009 to 2019. We enrolled patients with probable Alzheimer disease (AD) who had completed the Mini-Mental State Examination (MMSE) at least twice during follow-up, and who had BPH. We compared the difference in MMSE scores between patients who took tamsulosin for >1000 days and those who did not take any alpha-blocker. We tested the effect of tamsulosin on cognitive decline in patients with AD, using propensity score-matched logistic regression analysis. Eligible cases were included in the tamsulosin (n = 68) or no-medication (n = 153) groups. After propensity score matching, clinical characteristics such as educational attainment and vascular risk factors were similar in the tamsulosin and no-medication groups. The MMSE scores did not differ significantly between the tamsulosin and no-medication groups ( P = .470). The results suggest that tamsulosin for BPH is not associated with worsening of the cognitive decline in patients with AD.